Pengaruh Intensitas Aset Tetap, Tingkat Hutang Dan Kompensasi Dewan Komisaris Dan Direksi Terhadap Manajemen Pajak - Fadilah Nurfitriani; Angga Hidayat (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2021)
The aim of this study is to determine the impact on tax management of the fixed asset intensity, debt level, and compensation of the board of commissioners and directors in manufacturing companies listed on the Indonesian Stock Exchange. This is a quantitative analysis that employed the purposive sampling approach to obtain a sample of 29 businesses. The data used is secondary data from financial reports on manufacturing firms that were listed on the Indonesian Stock Exchange between 2015 and 2019. Multiple linear regressions used to evaluate the data. The findings indicate that the intensity of fixed assets has an effect on tax management, the amount of debt has no effect on tax management, and compensation for commissioners and directors has no effect on tax management. Simultaneously, the intensity of fixed assets, the amount of debt, and board of commissioners and director salaries all have a huge impact on tax management.